The Relationship Between Online Gaming Addiction and Learning Motivation Among High School Students: Hubungan Kecanduan Game Online dengan Motivasi Belajar Siswa SMA - Agustaf, Bryan Rafael; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Online game addiction is increasingly recognized as a factor affecting students’ academic performance. Specific Background: This study explores the relationship between online gaming habits and students’ learning motivation in senior high schools. Gap: Limited research has addressed how gaming addiction correlates with motivation in the context of Indonesian education. Aim: To analyze the relationship between online game addiction and students’ learning motivation. Results: Findings indicate a significant negative correlation between game addiction levels and students’ motivation, suggesting that higher gaming intensity leads to decreased learning engagement. Novelty: This research contributes by combining behavioral and motivational analysis to provide a comprehensive view of the impact of online gaming on learning motivation. Implications: The results offer insight for educators and parents to develop strategies to mitigate negative gaming behaviors and foster healthier study habits among students. Highlights: Negative correlation between game addiction and learning motivation Behavioral and motivational analysis combined Practical insights for educators and parents Keyword: Online Game Addiction, Learning Motivation, High School, Education Psychology, Student Behavior